Pengaruh Pemasaran Digital Pada Promosi Destinasi Wisata Kampung Adat Cirendeu Di Era Teknologi (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research aims to describe digital marketing management regarding promotions In tourist attractions, the Cirendeu traditional village is often little known. This background is designing, developing and promoting a destination for the purpose of achieving tourism benefits. This marketing focuses on creating sustainable relationships between tourism businesses and consumers by utilizing digital technology such as social media, websites and tourism applications. The problems found in the field are 1. internet limitations and lack of understanding of the importance of digital promotion 2. adaptation in digital era: Technology towards changes that continue to develop, 3. businesses in the tourism sector must have high creativity so that consumers can produce digital content with valuable quality according to their interests. The methods used include direct observation, interviews, distributing questionnaires and heritage studies. The results of this research show that the management of the Cirendeu Traditional Village tourist attraction does not understand digital-based promotion in the current era, due to internet limitations.Apart from that, this research can provide understanding and insight for Cirendeu traditional village tourism managers to be able to develop digital promotion strategies that are more effective and sustainable